Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1590/s0004-2803.202200001-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Early Nutritional Assessment and Intervention in Hospitalized Liver Cirrhosis Patients

Abstract: Background Malnutrition is common in liver cirrhosis patients that is correlated with early complications, morbidity and mortality. Objective The purpose of the study was to assess nutritional status, impact of nutritional screening and intervention in liver cirrhosis patients by evaluating their actual energy and protein intake during hospital stay. Methods A cross sectional study was conducted wherein all patients’ nutritional status was defined by Subjective Global Assessment tool. Adequate energy and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…2 Malnutrition has become an important cause of mortality in patients with cirrhosis, and the incidence increases with the disease severity. 26,27 The present study identified associations between the nutritional status of patients with cirrhosis and disease progression using validated screening assessment tools.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…2 Malnutrition has become an important cause of mortality in patients with cirrhosis, and the incidence increases with the disease severity. 26,27 The present study identified associations between the nutritional status of patients with cirrhosis and disease progression using validated screening assessment tools.…”
Section: Discussionmentioning
confidence: 93%
“…Liver dysfunction leads to malnutrition, which may develop insidiously in the early stages of chronic liver disease, eventually leading to protein‐energy malnutrition 2 . Malnutrition has become an important cause of mortality in patients with cirrhosis, and the incidence increases with the disease severity 26,27 . The present study identified associations between the nutritional status of patients with cirrhosis and disease progression using validated screening assessment tools.…”
Section: Discussionmentioning
confidence: 95%